Evaluation of the collection of the Asian Center Library, University of the Philippines a follow-up study - Cledera, Virgilio Ramel A.; Cabbab, Johann Frederick A. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1998)
This study was done to evaluate the collection of the Asian Center Library using the perceptions of the students from the Asian Center and those from other colleges. This study is a follow-up of the study made by Cecilia M. Dizon in 1982, which also evaluated the collection of the Asian Center Library.
The study used the Impressionistic method and the main research tool was the questionnaire. Most of the respondents were students who were from other colleges in U.P. and some students from the Asian Center.
The significant findings were:1) The primary reason why students and other library users visit the Asian Center Library is to do research;2) The collection of the Asian Center Library more or less satisfies the needs of its users;3) The collection of the Asian Center Library is fairly adequate which means it still lacks some materials like books, journals, etc.;4) Much of the collection of the Asian Center Library is up-to-date according to the users but the collection still needs some up-to-date materials;5) The collection of Asian countries that are found in the Asian Center Library is not that adequate although it offers its users a number of materials about Asian countries;6) The Asian Center Library has quite a strong collection.7) Many users find the information that they need in the Asian Center Library but because the library has a collection of materials that are not up-to-date, this affects the information reliability of the library.
Computer print out.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Libraries -- Evaluation. -- Philippines; University of the Philippines Diliman. Asian Center Library